Information Technology (IT) Improvement At PT. Sumber Alfaria Trijaya - Marisa Karsen (Bina Nusantara University, 2013)
Retail industry is the second largest industry after agricultural industry in terms of employment absorption in Indonesia. The situation of the quite dynamic retail industry is marked by the development of modern retail trade and it impacts on traditional markets and suppliers. PT Sumber Alfaria Trijaya, known as Alfamart is one of the best retail company in Indonesia. It already uses Supply Chain Management and B2B to support their operations. Alfamart also has its own website which provides information about products, outlets, services, and promo. This research discusses about IT improvement. The purpose of this paper is to improve Alfamart IT performance and make innovation on the IT to increase customer satisfaction. The methodology used is defining the problem, measure, analyst problem, improvement required by Alfamart, and control to monitor the implementation. Problems are identified using SWOT analysis, problem clarification, and business model canvas. Analyzing the problems, solution hypotheses and IT improvement are recommended for Alfamart.